Alternative model for micro enterprises’ human capital development in Malaysia - Mohd Thas Thaker, Mohamed Asmy; Mohamed, Mustafa Omar; Duasa, Jarita; Abdullah, Moha Asri (2013)
Micro enterprises (MEs) contribute significantly to respective economies in developed and developing countries alike including in Malaysia. The contributions of Malaysian MEs to the national economy can be measured in terms of some inter-related issues: economic (income generation), social (poverty reduction) and political (wealth redistribution). Despite these recognized importance and the largest contributor to SMEs - the micro enterprises have suffered from human resource deficiency. Most of them have less skilled human capital resources with low level of education, lack of experiences and improper trainings and programs. By using the content analysis to critically survey the literature on the subject, the present study aims to develop an Integrated Cash Waqf Micro Enterprise Investment (ICWME-I) model for micro enterprises in Malaysia that provides better human capital resources. This study proposes ICWME-I model as a solution for micro enterprises to overcome their human capital resource constraints and enhance their contributions to the national income. The study concludes with some suggestions for future research.